2018
DOI: 10.18632/aging.101495
|View full text |Cite
|
Sign up to set email alerts
|

Aging exacerbates mortality of Acinetobacter baumannii pneumonia and reduces the efficacies of antibiotics and vaccine

Abstract: Pneumonia caused by Acinetobacter baumannii has become a serious threat to the elderly. However, there are no experimental studies on the relevance between aging and A. baumannii infections. Here, we established an aged pneumonia mouse model by non-invasive intratracheal inoculation with A. baumannii. Higher mortality was observed in aged mice along with increased bacterial burdens and more severe lung injury. Increased inflammatory cell infiltration and enhanced pro-inflammatory cytokines at 24 hours post inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Also, the neutrophil depletion studies demonstrated an important pathogenic role for these cells during A. baumannii systemic infection (19). Our previous work showed that neutrophil infiltration with defective bacterial killing function contribute to the severe pneumonia in aged mice (16). The complex role of neutrophil in response to A. baumannii infection may be different in non-lethal model vs. lethal model, or in different stages of lethal infection, which needs further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the neutrophil depletion studies demonstrated an important pathogenic role for these cells during A. baumannii systemic infection (19). Our previous work showed that neutrophil infiltration with defective bacterial killing function contribute to the severe pneumonia in aged mice (16). The complex role of neutrophil in response to A. baumannii infection may be different in non-lethal model vs. lethal model, or in different stages of lethal infection, which needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…WT and Rag1 −/− mice were infected with A. baumannii as previously described (16). Briefly, Mice were intraperitoneally anesthetized with pentobarbital sodium (62.5 mg/kg) and then non-invasive intratracheally inoculated with different dose (2.5 × 10 6 CFU, 5 × 10 6 CFU, and 2 × 10 7 CFU) of A. baumannii in 20 µl PBS.…”
Section: Mouse Pneumonia Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We have established a pneumonia model as described previously [ 25 ]. In brief, mice ( n = 5) were anesthetized with pentobarbital sodium (62.5 mg/kg of body weight) [ 26 ] and then challenged with an appropriate dose of different strains of K. pneumoniae in a 20 μ l volume through noninvasive intratracheal inoculation. Mice were monitored for 7 days for survival rate and body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Their immune status is difficult to assess with current diagnostic methods but it predisposes for infections and antibiotic therapy. A study on A. baumannii pneumonia in aged mice illustrates that mortality increases with age, while efficacies of treatment, both antibiotics and vaccination, decrease because both rely on functional immune responses (79). Similarly, the human vaccine response is compromised by the immunodeficiencies caused by aging of the immune system [reviewed in (80,81)].…”
Section: Consequences For Design Of Efficacy Studiesmentioning
confidence: 99%